Different Effects of Thermophilic Microbiological Inoculation With and Without Biochar on Physicochemical Characteristics and Bacterial Communities in Pig Manure Composting - Sun, Likun; Long, Min; Li, Jianshu; Wu, Renfei; Ma, Lin; Tang, Defu; Lu, Yongli; Wang, Ziyu (Frontiers in Microbiology, 2021)
This study evaluated the effects of thermophilic microbial inoculation alone and with biochar on the physicochemical characteristics and bacterial communities in pig manure composting with wheat straw. Both, a single bacterial treatment and one with 10% coconut shell biochar added, accelerated the temperature increase rate. Thermophilic microbial added significantly reduce total nitrogen loss, integrated with biochar accelerate total organic carbon degradation. Firmicutes, Bacteroidetes, Actinobacteria and Proteobacteria as the major phyla in the composting. The relative abundance of genera was found to be dependent on the composting period and treatment. While genus Lactobacillus (26.88% 46.71%) and Clostridium_sensu_stricto (9.03% 31.69%) was occupied superior position in the temperature rise stage and Bacillus (30.90%-36.19%) was outstanding in the cooling stage. Temperature, TN, and ammonium nitrogen significantly influenced bacterial phyla composition. TN, water content, and nitrite nitrogen were the main drivers of bacterial genera communities. Further, our results demonstrate that microbial consortium plays a crucial role in nitrogen fixation for enrich Pseudomonas, whereas can accelerate TOC degradation when interacting with biochar for higher bacterial richness and diversity as well as overrepresented Corynebacterium.